2019
DOI: 10.1002/cm.21521
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes are mechanoresponsive to the microflow‐induced shear stress

Abstract: Here, we have reported that keratinocytes respond to the microflow‐induced shear stress both at the collective and individual cell level. Using a microfluidic setup, we categorically showed that low shear stress of magnitude 0.06 dyne/cm2 could induce morphological variation and cytoskeletal reorganization in keratinocyte, whereas higher shear stress (6 dyne/cm2) resulted in cellular disruption. Using a series of blocker molecules specific to different mechanotransducers, we demonstrated the pivotal role of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…Agarwall et al showed that epidermal keratinocytes are sensitive to microflow-induced shear stress [ 57 ]. These cells exhibited mechanoresponsive structural reorganization under the influence of shear stresses of magnitude 0.06 dyne/cm 2 and cellular damage under shear stresses of magnitude 6 dyne/cm 2 .…”
Section: Key Requirements For the Development Of Skin-on-a-chip Devicesmentioning
confidence: 99%
“…Agarwall et al showed that epidermal keratinocytes are sensitive to microflow-induced shear stress [ 57 ]. These cells exhibited mechanoresponsive structural reorganization under the influence of shear stresses of magnitude 0.06 dyne/cm 2 and cellular damage under shear stresses of magnitude 6 dyne/cm 2 .…”
Section: Key Requirements For the Development Of Skin-on-a-chip Devicesmentioning
confidence: 99%
“…[82] These stimuli can modulate cell behavior, inducing morphological changes, proliferation, migration and altering phenotypic expression leading to harmful or therapeutic impacts on skin health. [83,84] Substrate stiffness plays an important role in regulating cell morphology, adhesion, and phenotypic expression. [82] It is common for 3D skin models to include epidermal keratinocytes cultured on either cellular or acellular hydrogels with mechanical properties representative of the dermis.…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…However, epidermis exposure to shear stress during the culture process prior to ventilation has been shown to induce morphological variation, including polarization of columnar basal keratinocytes, cytoskeletal reorganization, improved epithelial phenotype, and thickening of the viable epidermis. [71,80] The magnitude of shear stress exposure on keratinocytes influences cell viability, with low shear stress, 0.06 dyne cm −2 , shown to improve the epidermal model and high shear stress, 6 dyne cm −2 , resulting in cellular disruption. [80] Hence, low shear, double-sided perfusion during cell culturing should be considered necessary to improve skin models.…”
Section: Perfusable Skin Modelsmentioning
confidence: 99%
“…[71,80] The magnitude of shear stress exposure on keratinocytes influences cell viability, with low shear stress, 0.06 dyne cm −2 , shown to improve the epidermal model and high shear stress, 6 dyne cm −2 , resulting in cellular disruption. [80] Hence, low shear, double-sided perfusion during cell culturing should be considered necessary to improve skin models.…”
Section: Perfusable Skin Modelsmentioning
confidence: 99%